The Effects of Asymetric Information, Inflation, BI Rate, and Exchange Rate on the Returns of LQ45 Stocks - Febriyanti, Ulima Digna; Tyas Danarti Hascaryani (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The purpose of this research is to determine the influence of the variables asymmetric information, inflation, BI rate, and the rupiah exchange rate on the return of LQ45 shares listed on the Indonesia Stock Exchange in 2018-2022. This research took samples from 23 companies listed on LQ45 of the Indonesian Stock Exchange in 2018-2022. This research uses a panel data regression analysis method. The panel data regression model chosen is the Common Effect Model (CEM). The research results show that the asymmetric information variable has a significant positive effect on stock returns and the inflation variable has a significant negative effect on stock returns. Meanwhile, the BI rate and rupiah exchange rate variables do not have a significant effect on the return of LQ45 shares listed on the Indonesia Stock Exchange for the 2018-2022 period.